A look at tourism in Serra de Itabaiana/SE: evaluation of its tourist potential (Research, Society and Development, 2020)
Given the importance of the tourist activity, it is noted the need and effort that managers have when planning tourism properly, seeking the economic, social, cultural and environmental sustainability of the receiving region. Thus, this article aims to analyze the existence of the tourist potential of Serra de Itabaiana/SE, using the methodology developed by Barcelos (2016). Data were collected through a survey with questionnaires applied in loco, semi-structured interviews, in addition to bibliographic, documentary research and direct observation. The results show that the Serra de Itabaiana has a high tourist potential, through the influence of its scenic beauty and unique aesthetics, due to the quantities and diversity of natural, cultural and religious resources, conducive to tourism development. This research made it possible to point out the need to monitor cargo capacity so that there are no negative impacts on the environment, such as working to foster the surrounding community for the development of community-based tourism.